Shahādah Istifādhah (Testimonium De Auditu) in Isbat Waqf Cases in Religious Courts from the Perspective of Fiqh and Civil Law - A. Zamakhsyari Baharuddin; Rifqi Qowiyul Iman; Andi Yaqub (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This paper examines how exactly the application of Shahādah Istifāḍah (the testimonium de auditu) in the case of wakaf determination which is brought to the Religious Court as a special Islamic civil judicial institution under the Supreme Court of the Republic of Indonesia. This research was analyzed using descriptive analytic method. In the discussion it is explained the comparative analytic the concept of Shahādah Istifāḍah with the concept of testimonium de auditu and its legal force in the case of proof in Court especially in the case of waqf determination. This paper concludes that the Shahādah Istifāḍah can be used as a means of proof in waqf determination.